Using Wikipedia to Develop 21st Century Skills: Perspectives from General Education Students - Marvi Remmik; Ann Siiman; Riina Reinsalu; Maigi Vija; Andrus Org (MDPI AG, 2024)
Purpose: The aim of the study was to find out how and why students use Wikipedia and what their attitudes are towards Wikipedia as a source of information for learning. Methodology: The article is based on a quantitative study in which 381 Estonian school children participated in filling out an online survey. The questionnaire included both multiple-choice and open-ended questions. Findings: Statistical analyses and responses to open-ended questions showed that students often use Wikipedia as a primary source of information, but that their use of the site for learning tasks is guided by teachers' attitudes and perceptions towards Wikipedia. Students perceive Wikipedia as a quick and convenient source of information but are uncertain about its reliability. Under teachers' guidance, they have learnt to search for information and to be source-critical, while more attention is needed to develop academic literacy, including both text comprehension and text composition. Value: As there is still very little research on how Wikipedia is used for learning purposes in general education schools, the results of the study contribute to further discussion on the potential of Wikipedia as an innovative teaching tool for different subjects.